1995
DOI: 10.1164/ajrccm.152.2.7633715
|View full text |Cite
|
Sign up to set email alerts
|

Increase in activated CD8+ cells in bronchoalveolar lavage fluid in patients with diffuse panbronchiolitis.

Abstract: To study the role of T cells in diffuse panbronchiolitis (DPB), we investigated T-cell subsets in bronchoalveolar lavage fluid (BALF) or 33 patients with DPB, nine patients with bronchiectasis, and 20 healthy volunteers. BALF from DPB patients contained a higher percentage of neutrophils than that from patients with bronchiectasis or healthy volunteers, whereas the percentage of lymphocytes was similar in the three groups. DPB patients, however, had a higher number of lymphocytes and a reduced CD4/CD8 ratio co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 27 publications
5
60
0
Order By: Relevance
“…The concentrations of IL-8 in BALF (815 pg·mL -1 ) and serum (79.7 pg·mL -1 ) were higher in our patient compared with those of five of the seven healthy volunteers (BALF 21± 46 pg·mL -1 ; serum 2.5±5.6 pg·mL -1 ) (table 1). More importantly, the levels of IL-8 in our patient were similar to those observed in DPB patients (BALF 375± 462 pg·mL -1 (n=15); serum 66.6±88.2 pg·mL -1 , (n=12)) [14] and in ARDS patients [11]. Therefore, IL-8 may contribute, at least in part, to neutrophil accumulation in the lungs of patients with WG.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The concentrations of IL-8 in BALF (815 pg·mL -1 ) and serum (79.7 pg·mL -1 ) were higher in our patient compared with those of five of the seven healthy volunteers (BALF 21± 46 pg·mL -1 ; serum 2.5±5.6 pg·mL -1 ) (table 1). More importantly, the levels of IL-8 in our patient were similar to those observed in DPB patients (BALF 375± 462 pg·mL -1 (n=15); serum 66.6±88.2 pg·mL -1 , (n=12)) [14] and in ARDS patients [11]. Therefore, IL-8 may contribute, at least in part, to neutrophil accumulation in the lungs of patients with WG.…”
Section: Discussionsupporting
confidence: 84%
“…To support our hypothesis, we studied the content of neutrophil-related cytokines and neutrophil products in BALF and serum or plasma of this patient. IL-8 is known to have a potent neutrophil chemotactic activity [10], and to play an important role in the accumulation of neutrophils in the lungs in the adult respiratory distress syndrome (ARDS) [11], idiopathic pulmonary fibrosis (IPF) [12] and diffuse panbronchiolitis (DPB) [13,14]. The concentrations of IL-8 in BALF (815 pg·mL -1 ) and serum (79.7 pg·mL -1 ) were higher in our patient compared with those of five of the seven healthy volunteers (BALF 21± 46 pg·mL -1 ; serum 2.5±5.6 pg·mL -1 ) (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of macrolides over human lymphocytes isolated from peripheral blood are also associated with apoptosis induction, which may be related to the anti-inflammatory actions of clarithromycin, azitromicin, and josamicin (Ishimatsu et al, 2004). It has also been shown that clarithromycin may reduce lymphocyte counts in the lungs of rats with respiratory infection caused by Pseudomonas aeruginosa (Mukae et al, 1995). Similar results were observed in studies on lung diseases in humans (Yanagihara et al, 1997).…”
Section: Discussionsupporting
confidence: 61%
“…After obtaining informed written consent from the subject, BAL was performed using a flexible fibreoptic bronchoscope (Olympus BF P-20; Olympus, Tokyo, Japan) under local anaesthesia of the upper airway with 2% lidocaine as described previously [19]. The bronchoscope was wedged into the subsegmental bronchus of the right middle lobe or, in patients with EP and BOOP, into areas of lung parenchyma otherwise normal on chest roentgenogram, and 150 or 200 mL normal saline was instilled in 50 mL aliquots.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%